Differential Photosynthetic Response of a Green Tide Alga Ulva linza to Ultraviolet Radiation, Under Short‐ and Long‐term Ocean Acidification Regimes. (13th March 2019) - Ma, Jing; Wang, Wen; Qu, Liming; Liu, Xiaoyan; Wang, Zhiqin; Qiao, Sen; Wu, Hailong; Gao, Guang; Xu, Juntian
Abstract: Both ocean acidification (OA) and solar ultraviolet (UV) radiation can bring about changes in macroalgal physiological performance. However, macroalgal responses to UV radiation when acclimatized to OA under different time scales are rare. Here, we investigate the response of Ulva linza, a green tide alga, to UV radiation in the form of photosynthetically active radiation (PAR) or PAB (PAR+UVA+UVB) radiation. Radiation exposures were assessed following long‐term (from spore to adult stage, 1 month) and short‐term (adult stage, 1 week) OA treatments. Results showed that increased CO2 decreased the damage rate ( k ) and repair rate ( r ) of thalli grown under short‐term OA conditions with PAB treatment, the ratio of r : k was not altered. Following long‐term OA conditions, r was not affected, although k was increased in thalli following PAB treatment, resulting in a reduced ratio of r : k . The relative level of UV inhibition increased and UV‐absorbing compounds decreased when algae were cultured under long‐term OA conditions. The recovery rate of thalli was enhanced when grown under long‐term OA after UV radiation treatment. These results show that blooming algae may be more sensitive to UV radiation in marine environments, but it can develop effective mechanisms to offset the negative effects, reflecting acclimation to long‐term OA conditions. Abstract : We investigate the response of Ulva linza to UV radiation in the form of photosynthetically active radiation or PAB radiation. Radiation exposures were assessed following long‐term and short‐term OA treatments. Results showed that increased CO2 decreased the damage and repair rate of thalli grown under short‐term OA conditions with PAB treatment. In thalli, k was increased following PAB treatment at long‐term OA conditions. These results show that blooming algae may be more sensitive to UV radiation in marine environments, but it can develop effective mechanisms to offset the negative effects, reflecting acclimation to long‐term OA conditions.